Estimating Fishing Seasons of Mackerel in Barru District: An Efficiency of Fishing Business and Effectiveness of Fisheries Management : Pendugaan Musim Penangkapan Ikan Kembung di Kabupaten Barru: Sebuah Upaya Efisiensi Usaha Nelayan dan Efektifitas Manajemen Perikanan - Muhammad Ridwan (Hasanuddin University, 2021)
The potential of Barru Regency waters with a coastline of about 78 km is used by several groups of purse seine fishermen as a business opportunity to make formations for mackerel fishing activities. This study aims to predict the pattern of mackerel fishing season in Barru Waters, and to simply describe environmental conditions as an effective fishing management instrument. This study uses CPUE time series data (catch per unit effort) from the Marine Fisheries Service of Barru Regency in 2017-2020 and interviews with several purse seine fishermen in the last year of 2021. In addition, satellite imagery of sea surface temperature (SST), current velocity and chlorophyll-a were also used to describe environmental conditions during the peak fishing season for the study period June-August 2021. The CPUE moving average time series analysis was used to calculate the fishing season index (IMP). The results showed that the peak season for mackerel fishing occurred in the east season around Barru Waters, precisely in June with IMP of 166%. This condition corresponds to warm temperatures, and relatively high chlorophyll concentrations. Such conditions create potential fishing grounds along the study area. This information on mackerel fishing season is very helpful in improving the quality of management of small pelagic fisheries in Barru and surrounding waters.